Cooling Media–Driven Shift in Dominant Machining Mechanisms: A Taguchi-Based Optimization of Surface Roughness in CNC Milling of S45C Steel - Faing, Fatullah; Yudo, Eko; Kurniawan, Zaldy (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Is to optimize the surface roughness in CNC milling of S45C steel using two types of cooling media: Dromus and radiator water. Methodology: This study employed the Taguchi experimental design method to compare cooling media. Three main machining parameters, namely spindle speed, depth of cut, and feed rate, were examined at three levels using a Taguchi L9 orthogonal array. In addition, two different cooling media, namely radiator water and Dromus, were applied to investigate their effects on surface integrity. Surface roughness values ​​were measured using a standard surface roughness tester and analyzed using the Signal-to-Noise (S/N) ratio, with the results supported by Analysis of Variance (ANOVA). Main Findings: The results demonstrate that cooling media play a decisive role not only in reducing surface roughness but also in shifting the dominant machining parameter. Under radiator water cooling, spindle speed was the most influential factor, contributing 45.67% to surface roughness variation. In contrast, when Dromus was applied, depth of cut became the dominant parameter with a contribution of 63.40%. Dromus consistently produced lower surface roughness values and higher S/N ratios, indicating improved thermal control and process stability. The optimal machining condition was identified at a spindle speed of 1910 rpm, a depth of cut of 0.2 mm, and a feed rate of 330 mm/min. Novelty/Originality of this study: The novelty of this study lies in revealing how cooling media fundamentally alter surface formation mechanisms and parameter dominance, offering new insights for adaptive and efficient CNC milling optimization strategies.